Produção de sinalário em LIBRAS para equipamentos laboratoriais utilizados no Ensino Tecnológico na área de produção de açúcar e álcool - Rodrigues, Rogério Pacheco (2022)
The theme of this dissertation arises from academic experiences as a student in the field of Chemistry, especially those provided during the course of the Degree in Chemistry at the Federal Institute of Goiás (IFG) - Campus Itumbiara, in the period between 2012 and 2017. Thus, it is observed that one of the difficulties in the teaching and learning process in technical and professional education for deaf students is related to symbology/language. This is intensified in experimental classes, since various equipment is used, whose nomenclature is mentioned during the teaching and learning process, names that both deaf students and Libras interpreters do not know. In this context, this research aimed to develop a sign in Libras for laboratory equipment used in Technological Education in the area of sugar and alcohol production. The methodological path used was the mapping of 6 (six) pieces of equipment used in the practical classes of the curricular component of the Sugar and Alcohol Manufacturing Process of the Sugar and Alcohol Production Auxiliary course, offered by the National Service for Industrial Learning (SENAI ) and definitions, in the case of the Portuguese language, and the creation and registration of term signs in the Brazilian Sign Language. It is noteworthy that the development of signs relied on the presence of a deaf person, since a sign cannot be created without the presence, help and acceptance of the deaf community. The organization of the material was based on the grammatical parameters of the Brazilian Sign Language, which are: hand configuration, point of articulation, hand orientation, movement, and non-manual expression. This signal is disclosed through the access link to the website available in chapter 7 of this dissertation. Finally, it is highlighted that the material aims to contribute to an inclusive education and standardization of the special chemistry language.